LITERATURE REVIEW ON THE ANALYSIS OF MOTIVATIONAL ELEMENTS AND GAMIFICATION CONTENT IN CREATING SEMANTIC BARRIERS - Carlos Rugu, Anida Sarudin, Zulkifli Osman, Husna Faredza Mohamed Redzwan, Wan Mazlini Othman, Marlini Idris (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to examine the development of literature highlights related to motivational elements and gamification content in the implementation of gamification which indirectly creates semantic barriers. A total of 11 local and international literature were examined based on Literature Review Inventory (IVS), which was built on ARCS Model founded by John Keller (2010), consisting of 4 important elements: attention, relevant, confidence and satisfaction as well as referring to Content Gamification Model by Karl M. Kapp et Al (2014) which consist of 7 elements: story, challenge, curiosity, character, interactive, feedback and freedom to fail. Both models focused on four (4) teaching and learning motivational factors in gamification as well as in the aspects of gamification content which are the basic backup in fulfilling the teaching and learning based on gamification. The findings discovered that the main relationship between semantic barrier and gamification process was through meanings with an attempt to deliver the design and implementation of gamification. Barriers of meaning which occur could be the result of some semantic aspect: the barrier of an understanding of motivational concept in gamification based on ARCS Model, gamification elements such as point, badges, levels, leader boards, challenges, reward, on boarding and engagement loops as well as the concept of the fun and implementation of gamification design. This study is important in the effort to expose various constraints and obstacles in the gamification process which needs to be given the attention though the method is interactive and entertaining in nature.